Can the Latin American and Caribbean countries emulate the Irish model of FDI attraction? - Rios-Morales, Ruth (2006)
Highlights important aspects of the Irish experience that may be applicable in Latin America. Assesses the role of FDI in the economy and looks at recent trends and determinants of FDI in developing countries. Evaluates FDI strategies and identifies policy failures in the era of globalization in those countries. Examines the Irish model of FDI attraction, highlighting the importance of the work of promotional agencies.